The Kumagai Method Using the Pigeon Long Nipple for Dealing With Various Movements While Bottle Feeding Children With Cleft Lip And/or Palate: A Qualitative Descriptive Study - Eri Nagatomo; Yukari Kumagai; Yumi Hirai; Shoko Miyauchi; Takuro Inoue; Qi An; Eri Tashiro; Junko Miyata; Shingo Ueki (Health Science Reports, 2025)
ABSTRACT Background and Aims Feeding poses a significant challenge for children with cleft lip and/or palate. The Kumagai method, a specialized approach for feeding these children, has been developed; its fundamental techniques have already been published. However, children often exhibit varied reactions to feeding, such as refusal and resistance. If not managed appropriately, these responses can hinder feeding progress. This study aimed to identify strategies for addressing different feeding‐related movements in children with cleft lip and/or palate during bottle feeding. Methods In September 2022, five specialist nurses from a Japanese urban university, all trained in the Kumagai method—an experimental nursing procedure involving bottle feeding with a long‐nipple bottle—participated in this descriptive study. Structured interviews were conducted to explore techniques for managing feeding‐related movements, covering 14 scenarios that encompassed children's oral reactions and gross motor movements before, immediately before, and during feeding. Results The participants described their techniques for handling each scenario. Some strategies followed a predefined order of priority, while others were adapted based on the intensity of the child's movements. Additionally, some strategies were chosen according to the nurses' assessments of the child's needs. Conclusions The Kumagai method emphasizes observing a child's reactions and movements, interpreting their significance and applying appropriate handling strategies accordingly. These assessments and tailored interventions might help children develop a natural feeding posture, ultimately fostering their acceptance of and willingness to feed using a long‐nipple bottle.